Fabrication of high-resolution nanostructures of complex geometry by the single-spot nanolithography method - Samardak, Alexander; Anisimova, Margarita; Samardak, Aleksei; Ognev, Alexey (Beilstein Journal of Nanotechnology, 2015)
The paper presents a method for the high-resolution production of polymer nanopatterns with controllable geometrical parameters by means of a single-spot electron-beam lithography technique. The essence of the method entails the overexposure of a positive-tone resist, spin-coated onto a substrate where nanoscale spots are exposed to an electron beam with a dose greater than 0.1 pC per dot. A single-spot enables the fabrication of a nanoring, while a chain of spots placed at distance of 5–30 nm from each other allows the production of a polymer pattern of complex geometry of sub-10 nm resolution. We demonstrate that in addition to the naturally oxidized silicon substrates, gold-coated substrates can also successfully be used for the single-spot nanopattering technique. An explanation of the results related to the resist overexposure was demonstrated using Monte Carlo simulations. Our nanofabrication method significantly accelerates (up to 10 times) the fabrication rate as compared to conventional lithography on positive-tone resist. This technique can be potentially employed in the electronics industry for the production of nanoprinted lithography molds, etching masks, nanoelectronics, nanophotonics, NEMS and MEMS devices.
Keywords: electron-beam lithography; exposure dose; high-resolution lithography; nanomagnets; nanostructure; overexposure; PMMA; polymer; resist carbonization